Efeitos da prolactina sobre a massa óssea de ratas ovariectomizadas - Driusso, Patricia (2003)
Prolactin (PRL) has a great number of biologic functions in many species. Beyond the well known effects on reproduction, lactation and maternal behavior, many studies have showed the effects of PRL on the mineral transportation, calcium metabolism and bone. PRL seems to have an effect on the bone, acting direct or indirectly. The aim of this study was to investigate the effects of the PRL on bone mass of female ovariectomized (ovx) Wistar rats, through physical, biomechanical and biochemical analysis of the femur, biochemical of serum and densitometry of the tibia. The rats had 4 months of age in the beginning of the study and were divided in 3 groups: basal group, hiperPRL group (intact, ovx+sham e ovx + 2 grafted anterior pituitary under the kidney capsule) and hipoPRL group (intact+saline, ovx+saline and ovx rats treated with bromocriptina-3 mg/Kg). Statistical analysis of results was performed by a two way analysis of variance (ANOVA) followed by a Student Duncan test. The ovx promoted the figher weight gain and bone growth. It was observed that the ovx+hipófise group showed a significant decreased in maximum force and stiffness when compared with the intact group, and a significant decreased in the densitometry, mineral bone density and percentage of mineral material of the femur when compared with the ovx+sham group. The ovx+ bromocriptine group showed a significant increase in maximum force, stiffness and bone volume of the right femur and the bone mineral content of the tibia when compared with the ovx+saline and basal groups. The lack of the PRL maintains the biomechanical parameters of the ovx rats statistically equal to the intact animals, showing a protective action of the PRL against the osteopenic effect promoted by ovariectomy.